2016
DOI: 10.1007/s12298-016-0359-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial secondary metabolites ameliorate growth, in planta contents and lignification in Withania somnifera (L.) Dunal

Abstract: In the present investigation, metabolites of Streptomyces sp. MTN14 and Trichoderma harzianum ThU significantly enhanced biomass yield (3.58 and 3.48 fold respectively) in comparison to the control plants. The secondary metabolites treatments also showed significant augmentation (0.75-2.25 fold) in withanolide A, a plant secondary metabolite. Lignin deposition, total phenolic and flavonoid content in W. somnifera were maximally induced in treatment having T. harzianum metabolites. Also, Trichoderma and Strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Nonetheless, it has been shown that Trichoderma harzianum may induce EO accumulation through direct intervention of its metabolites on the EO biosynthetic pathways, despite such an effect depending on the Ocymum species [ 83 ]. These effects may have been due, in our experiment, to a direct effect of both fungi on the phenylpropanoid, mevalonate, carotenoid and oxylipins pathway, as seen in tomato and other species when inoculated with AMF, Trichoderma or beneficial bacteria [ 84 , 85 , 86 , 87 ] so that at the one time the plant antioxidant status was relieved by the presence and activity of the microbial partner and, at the other time, such pathways may have been directly affected by some microbial metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it has been shown that Trichoderma harzianum may induce EO accumulation through direct intervention of its metabolites on the EO biosynthetic pathways, despite such an effect depending on the Ocymum species [ 83 ]. These effects may have been due, in our experiment, to a direct effect of both fungi on the phenylpropanoid, mevalonate, carotenoid and oxylipins pathway, as seen in tomato and other species when inoculated with AMF, Trichoderma or beneficial bacteria [ 84 , 85 , 86 , 87 ] so that at the one time the plant antioxidant status was relieved by the presence and activity of the microbial partner and, at the other time, such pathways may have been directly affected by some microbial metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study suggested that there were certain elicitors in the microbial cultures which played a vital role in enhancing the phenolic content of R. o cinalis leaves. Several studies have likewise reported the promising effect of endophytic bacteria in boosting phenolics and avanoid contents in Withania somnifera (L.), Dunal, and sweet basil (Gupta and Pandey 2015;Singh et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…B. monnieri plants were harvested 5 weeks after the inoculation of pathogen, M. incognita . For imaging lignification pattern, the transverse sections of stem were examined under fluorescent microscope DMI 3000 B (Leica, Wetzlar, Germany) with a wide range of wavelengths (250–700 nm) to induce autofluorescence 13 . For callose detection, leaves were boiled in ethanol and placed in 0.01% aniline blue for 1 h. The samples were examined for the presence of cell wall deposition using a UV epifluorescence microscope 48 .…”
Section: Methodsmentioning
confidence: 99%
“…To keep pace with the growing demand of this medicinal plant and considering its ability to grow under natural conditions, the present study was undertaken to develop strategies to improve yields of B. monnieri through beneficial microbial intervention. Previously, numerous methods have been employed to enhance plant immunity and the production of bioactive metabolites by the association between plant-beneficial microbes and their host plant (s), which suggests that the microbial partners could have a significant effect on host physiology 13 14 . However, till date, no information is available regarding the potential and possible mechanisms of the synergistic mode of microbes in the accumulation of secondary metabolites along with the modulation of the defense signaling pathway to endure biotic stress.…”
mentioning
confidence: 99%